1998
DOI: 10.1074/jbc.273.12.7044
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Rat Brain Phospholipase D Isozyme

Abstract: We have recently cloned a cDNA encoding a phospholipase D (PLD) from rat brain and named it rPLD1. It shows 90% amino acid identity with the human PLD isoform hPLD1b. We have expressed rPLD1 as a histidine-tagged fusion protein in insect (Sf9) cells using the expression vector pBlueBacHis and purified the recombinant protein to homogeneity by Ni 2؉ -agarose affinity chromatography. Phosphatidylinositol 4,5-P 2 and phosphatidylinositol 3,4,5-P 3 activated the PLD equipotently, but other acidic phospholipids wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
3

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 49 publications
9
94
3
Order By: Relevance
“…We have also observed that rPLD1 and PKC␣ are associated in Sf9 cells and that the interaction is enhanced by treatment of the cells with phorbol ester. 2 Furthermore, direct interaction between these proteins is indicated by in vitro findings (25,36). The association of rPLD1 with the PDGF receptor is somewhat surprising, although the fact that it is not enhanced by PDGF is to be expected since this PLD isoform has no recognizable SH2 or PTB domains (24,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also observed that rPLD1 and PKC␣ are associated in Sf9 cells and that the interaction is enhanced by treatment of the cells with phorbol ester. 2 Furthermore, direct interaction between these proteins is indicated by in vitro findings (25,36). The association of rPLD1 with the PDGF receptor is somewhat surprising, although the fact that it is not enhanced by PDGF is to be expected since this PLD isoform has no recognizable SH2 or PTB domains (24,36).…”
Section: Discussionmentioning
confidence: 99%
“…We have cloned and characterized a rat brain phospholipase D isozyme (rPLD1) (24,25). In the present study, we have investigated the effect of hydrogen peroxide as a pharmacologic agent on tyrosine phosphorylation and activation of rPLD1 in Swiss 3T3 fibroblasts.…”
mentioning
confidence: 99%
“…In mammalian cells, the molecular identities of the two isozymes of PLD, PLD 1 and PLD 2 , have been elucidated. Among these two isozymes, PLD 1 is activated by PMA both in vivo and in vitro through an activation of protein kinase C␣ (39). Although information about PLD isozyme(s) in Sf9 insect cells is limited (40), the observation that PMA stimulated LPA formation in Sf9-mPA-PLA 1 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have cloned a PLD1 isoform from rat brain (rPLD1) and have studied its properties in vivo and in vitro (7,9,26,27). Our previous study of this isoform showed that N-terminal or C-terminal fragments containing only one of the HKD domains did not have PLD activity when expressed in COS7 cells (10).…”
Section: Phospholipase D (Pld)mentioning
confidence: 99%